The literacy process of children in the early years of schooling - Suzano, Auriceli de Lima (Seven Editora, 2024)
This article aims to analyze how children build their thoughts while literacy, presenting the discussions of the works of Emilia Ferreiro and Ana Teberosky, Ana Smolka and Magda Soares. Blacksmith in his works presents us with the writing hypotheses that are constructed by children in the literacy phase. These writing hypotheses are elaborated by the children as they walk the path of reading/writing acquisition, until they reach the domain of functioning of the mother tongue. The child needs the interventions and mediation of his teacher during this initial stage of literacy of reading and writing of his language, while the child acquires knowledge and becomes a literate reader in the Brazilian Portuguese language. This article has the interest of a dissertation on how literacy teachers from the early years of schooling have understood about the elaboration of writing hypotheses of children during this school experience. DOI:https://doi.org/10.56238/sevened2024.009-038